Evaluation of Nitric Oxide Activity of Torilis Leptophyllain Indomethacin Induced Gastric Ulcer in Mice - batool, Saba; Noreen, Saima; Malik, Tooba; Fatima, Javaria; Shaheen, Bushra; Qammar, Sheikh Maria (Pakistan Armed Forces Medical Journal, 2023)
Objective: To evaluate the Nitric Oxide activity of Torilis leptophylla in Indomethacin-induced gastric ulcers in mice. Study Design: Laboratory-based experimental study Place and Duration of Study: Pharmacology Department, University of Health Sciences, Lahore Pakistan, from Jan to Dec 2016. Methodology: Thirty-six adult healthy male BALB/C mice with a weight range of 25-35 g were equally divided into six groups and designated as Group-I (Control), Group-II (Positive Control), Groups III to V (Torilis leptophylla extract trial Groups) and Group-VI (Omeprazole). Gastric ulceration was induced by a single dose of Indomethacin (20mg/kg) in Groups II–VI. The plant extract was administered in Groups III-V (100, 200, 300 mg/kg) whereas Omeprazole (3mg/kg) in Group-VI by gavage daily for three days as treatment of gastric ulceration. Nitric Oxide content was measured in gastric juice and serum of all groups by Nitric Oxide assay kit. Results: The positive Control-Group showed little Nitric Oxide in gastric juice and serum. Torilis leptophylla treated Groups (100 mg/kg, 200mg/kg and 300 mg/kg) showed significantly raised Nitric Oxide content in both gastric juice and serum than the Control Group (p<0.001). Conclusion: The study has determined that Torilis leptophylla possesses antiulcer and mucosal protective effects owing to the antioxidant activity of nitric oxide. This supports the use of the plant for the treatment of gastric ulcers.